Bridging family language policy and Arabic language acquisition by Indonesian Muslim community: A conceptual approach - Arifianto, Muhammad Lukman; Purnamawati, Zulfa; Izzudin, Iqbal Fathi; Mujahidah, Zulfa Azalia (Fakultas Sastra Universitas Negeri Malang, 2024)
Family language policy encompasses various aspects, such as identity, cultural heritage, communi-cation, education, and social integration within a family or community. Previous research has pri-marily focused on the use and preservation of native languages within multilingual societies, leav-ing a gap in understanding the relationship between family language policies and the acquisition of foreign languages in a familial setting. Consequently, this study presents a conceptual approach that explores key concepts and variables relevant to the family language policy approach, specifical-ly regarding the acquisition of Arabic by the Indonesian Muslim community. By analyzing the con-nection between the family language policy approach and variables related to foreign language acquisition, we hypothesized that the learning or acquisition of Arabic among Indonesian Muslims can be influenced by the language policy implemented within their families. Muslim parents play a crucial role in this process, both ideologically and practically, by providing an optimal learning envi-ronment and motivation for their children. As the family language policy involves decisions and practices governing language use and learning within the family context, it encompasses Muslim parents' choices regarding the Arabic language used at home, its application in specific activities, and their support for their children’s learning.